"I took physical lessons for granted": A case study exploring students' interpersonal interactions in online synchronous lessons during the outbreak of COVID-19. (April 2022) - Alger, Mari; Eyckmans, June
Abstract: The coronavirus pandemic presented a unique opportunity to observe how students interact and relate to each other in a new learning environment. This exploratory case study examines students' interpersonal interactions which occurred in online synchronous lessons during the initial stages of the outbreak. The language-focused content analysis of text-based chat data and thematic analysis of reflection answers collected from 40 students enrolled on an English as a Foreign Language (EFL) university course in Belgium is guided by the concept of social presence (SP) from the Community of Inquiry (CoI) theoretical framework and further complemented by a qualitative interpersonal pragmatics approach drawing on relational work. While all of the SP indicators were observed across the eight lessons, explicit acknowledgement of others in the learning environment was the most prevalent and seemed to boost affective and cohesive effects. Furthermore, the findings illustrated the importance students placed on having in-class opportunities to express their frustrations. A linguistic analysis of one such "venting" episode illuminated how a relational chain of events unfolded through students' use of a variety of SP indicators. Despite exuding a negative quality at first glance, the indicators generated immediate, positive relational effects such as enhancing students' feelings of belongingness.